PENGARUH KUALITAS PERUMAHAN TERHADAP KEPUTUSAN NASABAH DALAM RUMAH BERSUBSIDI (KPR) DI BANK MUAMALAT KCU MEDAN BARU - Dede Endrico; Saparuddin Siregar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of housing quality on customer decisions in choosing subsidized housing (KPR) at Bank Muamalat KCU Medan Baru. The research method used is qualitative with a field study approach. Data were collected through observation and in-depth interviews with the Branch Manager of Bank Muamalat KCU Medan Baru. The results showed that housing quality has a significant influence on customer decisions. The most dominant factors of housing quality are the quality of buildings and basic infrastructure, strategic location, housing facilities, and a safe and comfortable environment. Bank Muamalat needs to continuously improve the quality standards of housing financed through subsidized mortgages and tighten supervision of developers.